The role of human capital management in enhancingengagement and retention among top talent inorganization : a critical literature review / Roshidi Hassan - Hassan, Roshidi (Universiti Teknologi Mara Selangor, 2016)
In this challenging global economic, organizations are fighting in the war of talent to remain competitive. It is no doubt that the role of human capital management (HCM) is the upmost important for organization and there are many aspects of HCM that can be applied and used by human capital practitioners. On the other hand, the organization needs to understand the many aspects of HCM and try to link it in order to make employees engage and retain in the organization especially the top talent. Employees who are engaged are said to become more committed to the organization and thus build some emotional link between the employees and employer, which in turn lead to retention. Detailed literature review was undertaken to explore the role of HCM in enhancing engagement and retention among the top talent. Through the literatures reviewed, it was found that several HCM practices such as creating great work environment, encouraging positive discretionary behaviour, and competitive reward and recognition had actually help in enhancing employee's engagement. While some HCM practices also such as equitable reward package, continuous training and development program, and fair performance appraisal significantly contributed to employee's retention. Hence, this paper will focuses on discussing the role of HCM as a vital component to enhance engagement and retention of top talent based on findings and suggestions from reviewing the vast literatures.